Turkish League Against Rheumatism (TLAR) Recommendations for the Pharmacological Management of Rheumatoid Arthritis: 2018 Update Under Guidance of Current Recommendations - (:unkn) unknown (My University, 2018)
Objectives: This study aims to report the assessment of the Turkish League Against Rheumatism (TLAR) expert panel on the compliance and adaptation of the European League Against Rheumatism (EULAR) 2016 recommendations for the management of rheumatoid arthritis (RA) in Turkey. Patients and methods: The EULAR 2016 recommendations for the treatment of RA were voted by 27 specialists experienced in this field with regard to participation rate for each recommendation and significance of items. Afterwards, each recommendation was brought forward for discussion and any alteration gaining ≥70% approval was accepted. Also, Turkish version of each item was rearranged. Last version of the recommendations was then revoted to determine the level of agreement. Levels of agreement of the two voting rounds were compared with Wilcoxon signed-rank test. In case of significant difference, the item with higher level of agreement was accepted. In case of no difference, the changed item was selected.Results: Four overarching principles and 12 recommendations were assessed among which three overarching principles and one recommendation were changed. The changed overarching principles emphasized the importance of physical medicine and rehabilitation specialists as well as rheumatologists for the care of RA patients in Turkey. An alteration was made in the eighth recommendation on treatment of active RA patients with unfavorable prognostic indicators after failure of three conventional disease modifying anti-rheumatic drugs. Remaining principles were accepted as the same although some alterations were suggested but could not find adequate support to reach significance. Conclusion: Expert opinion of the TLAR for the treatment of RA was composed for practices in Turkish rheumatology and/or physical medicine and rehabilitation clinics.
Keywords: Romatoloji